Unleashing the Value of Lifelong Learning Institutes: Research and Practice Insights From a National Survey of Osher Lifelong Learning Institutes. Issue 3 (August 2019) - Talmage, Craig A.; Hansen, Robert Jack; Knopf, Richard C.; Thaxton, Steven P.; McTague, Riley; Moore, David Bennett
Lifelong learning as a field has leapt forward, but work remains to inform the structuring and practice of lifelong learning institutes. This study furthers the field of institution-based lifelong learning by utilizing cross-institutional research regarding the value of lifelong learning to older adults. A content analysis coding approach is undertaken to categorize and organize 4, 400 lifelong learners' responses to the question: "What about your Osher Institute has been valuable/important to you?" Responses came from 12 institutes across the United States. The organization and interpretation of the themes fell along four dimensions: (a) learning experience, (b) community environment, (c) learning quality, and (d) learning access. Subthemes within each of the four broad themes are identified and discussed. Slight demographic differences regarding codes assigned are highlighted. Institutional differences were more notable demonstrating that the structures and practices of institutes warrant more research.